An Evaluation of Fish Scales as Potential Adsorbents:pH and Concentration Effect - Abdullah, Bawadi; Vo, Dai-Viet N. (Trans Tech Publications, 2014)
Experimental investigations on removal of lead contamination from polluted water by adsorption technique using local fishes i.e.Tilapia and Merah (Oreochromos and Lutjanus) fish scales. The fish scales adsorbent equilibrated nearly approaching 100% of Pb uptake over the range of concentrations and pH studied. Unexpectedly, the performance of fish scales as an adsorbent is better as compared to commercially available activated carbon.